Pengembangan Konten Media Sosial Instagram Desa Jabung Klaten untuk Meningkatkan Keterlibatan Audiens - Putri, Visella Tania Radita; Wicaksono, Bintarto; Jatisidi, Artyasto (Jurnal Ilmiah Multimedia dan Komunikasi, 2024)
Currently, most village governments use social media to share information about the village, to introduce the village's potential, and to interact with villagers and the wider community. However, the Jabung Village Government does not yet have a social media account as an information channel. Therefore, the author aims to create a social media account to achieve one of the village's missions. This study discusses the content strategy on the main social media platform, Instagram, for the Jabung Village Government, Klaten, to increase engagement. This strategy aims to make the potential of Jabung Village more widely known. The author selects a strategy that aligns with the target audience and uses effective as well as engaging communication to ensure that all information is conveyed well and interaction with the audience is established. The Instagram content strategy is also designed according to the needs of the audience, especially the residents of Jabung Village. The method used is qualitative, with data collection through observation, interviews, and literature studies. The conclusion of this strategy shows that using attractive content titles is the most effective strategy to increase engagement, and the most effective content is Playful Content on Instagram story, utilizing interactive features such as polling and question boxes.